Tasks on the development of students' speech and thinking in the primary language and reading literacy classes (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This article discusses the importance of tasks in the development of oral and written speech of primary school students, as well as their thinking. Emphasis is placed on the use of assignments in the course of the lesson.